The Mediating Role Of Capital Structure In Corporate Governance On Firm Performance Of Family Companies - Iskandar Itan; Vinnie Chelencia (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2022)
This study looks into the relationship of the performance of family businesses in Indonesia and its corporate governance. It also investigates the mediation effect of capital structure on this relationship. Board size, independent commissioner, female director, ownership concentration, managerial ownership, audit committee meetings are used as indicators of GCG measurement. Capital structure is measured by leverage. ROA and Tobin's Q are used as indicators of measurement of firm performance. The panel data approach will be employed, using a sample of 117 companies registered on the Indonesia Stock Exchange between 2016-2020. The result of the study revealed the significant effect of board size, managerial ownership, and ownership concentration on the performance of the family businesses analysed, as measured by ROA. However, the result of the analysis using Tobin’s Q measure shows an insignificant effect. Furthermore, this study found capital structure to have a mediation effect on GCG and performance of a family business, through ownership concentration and managerial ownership.  Keywords: capital structure, firm performance, GCG.